A Stereoselective Catalytic Nitroaldol Reaction as the Key Step in a Strategy for the Synthesis of the Renin Inhibitor Aliskiren. Issue 11 (2nd March 2015) - Rossi, Sergio; Benaglia, Maurizio; Porta, Riccardo; Cotarca, Livius; Maragni, Paolo; Verzini, Massimo
Abstract: Aliskiren is the first‐in‐class orally active direct renin inhibitor. It was approved in 2007 for the treatment of hypertension. We have designed a new strategy for the convergent synthesis of aliskiren that involves a catalytic stereoselective nitroaldol reaction as the key step. A new enantiopure nitroalkane (synthonA 1 ), prepared in only three steps from a commercially available enantiopure 2‐(arylmethyl)‐3‐methyl butanol derivative, was successfully used in a copper‐catalysed Henry reaction to give a nitrolactone intermediate in which the correct configuration for the final product was established at all four stereocentres. Nitro‐group reduction, Boc‐protection of the resulting amine, aminolysis of the lactone with 3‐amino‐2, 2‐dimethylpropionamide, and finally Boc‐deprotection led to the enantiopure renin inhibitor aliskiren. Abstract : A new strategy for a convergent synthesis of the first‐in‐class orally active direct renin inhibitor aliskiren has been developed.